Enacting a just and sustainable blue economy through transdisciplinary action research - Heidkamp, C. Patrick; Garland, Michaela; Krak, Louie (The Geographical Journal, 2021)
To enact a just and sustainable blue economy, one must consider all the actors involved in its shaping. This paper argues that a quintuple helix approach to stakeholder engagement – involving government, academia, the business community, and civil society – and an inclusive transdisciplinary action research (TAR) methodology are promising avenues with which to do so. Embracing critical pragmatism as a foundational framework, key ideas from three strands of research are consolidated: (1) the recent work on the geographical dimension of socio-technical sustainability transitions; (2) the literature on just sustainabilities and just transition; and (3) action research and transdisciplinary approaches to problem solving. This allows for the reimagination of a common future for the blue economy that is developed through a different kind of democratic process driven and informed by co-learning, and shared experiences. By adopting a transdisciplinary action research approach, actors from different disciplines and spheres of experience can gain a better mutual understanding and find commonality through the open door of collaboration. The theoretical argument presented in this paper is illustrated by a vignette of an ongoing TAR project at Southern Connecticut State University, which outlines the challenges and opportunities inherent to implementing a TAR approach. The information, practices and views in this article are those of the author(s) and do not necessarily reflect the opinion of the Royal Geographical Society (with IBG). © 2021 The Authors. The Geographical Journal published by John Wiley & Sons Ltd on behalf of Royal Geographical Society (with the Institute of British Geographers)
Keywords: dept.egm; peer-reviewed